2015
DOI: 10.1097/ftd.0000000000000182
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Genetic Polymorphism of CYP3A5 and CYP2C19 and Concomitant Use of Voriconazole on Blood Tacrolimus Concentration in Patients Receiving Hematopoietic Stem Cell Transplantation

Abstract: In HSCT recipients, the variability of intravenous TAC concentration in the blood could be explained in part by the genetic variation of CYP3A5. The study results also strongly imply that the magnitude of hepatic interaction between TAC and VRCZ is affected by the genetic polymorphism of both CYP3A5 and CYP2C19 genes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 24 publications
2
23
0
Order By: Relevance
“…The strong inhibition of CYP3A4 by VRC in the small intestine and liver is likely to be the main mechanism of these DDIs. The magnitude of the interaction between VRC and tacrolimus was found to be affected by CYP3A5 polymorphisms as well as by CYP2C19 polymorphisms that result in different VRC exposure . It was shown that VRC could increase intracellular cyclosporine concentrations via inhibiting the P‐glycoprotein‐mediated transport of cyclosporine .…”
Section: Discussionmentioning
confidence: 99%
“…The strong inhibition of CYP3A4 by VRC in the small intestine and liver is likely to be the main mechanism of these DDIs. The magnitude of the interaction between VRC and tacrolimus was found to be affected by CYP3A5 polymorphisms as well as by CYP2C19 polymorphisms that result in different VRC exposure . It was shown that VRC could increase intracellular cyclosporine concentrations via inhibiting the P‐glycoprotein‐mediated transport of cyclosporine .…”
Section: Discussionmentioning
confidence: 99%
“…These polymorphisms can also influence the magnitude of DDIs between azoles and immunosuppressants [11,12]. The details of the interplay between DDIs and genetic variability in metabolizing enzymes are beyond the scope of this review and will not be further discussed.…”
Section: Introductionmentioning
confidence: 97%
“…found that the magnitude of CsA level increment did not correlate with plasma concentrations of oral voriconazole. [711] We identified a significant correlation between trough plasma concentration of voriconazole and the increase in the CsA C/D ratio in Iranian population, and our results suggest that the magnitude of drug interaction between CsA and voriconazole is affected by the plasma concentration of voriconazole. However, after subanalysis it was found that this correlation did not exist in patients who received voriconazole orally as has been demonstrated previously in Japanese population.…”
Section: Discussionmentioning
confidence: 62%
“…However, after subanalysis it was found that this correlation did not exist in patients who received voriconazole orally as has been demonstrated previously in Japanese population. [711] Genetic polymorphism of CYP3A4, CYP3A5, and CYP3A7 seems to be a relevant reason for this absence of correlation. [1213] In patients received voriconazole orally, both hepatic and GI CYP heterogeneity may be contributed to this wide variability.…”
Section: Discussionmentioning
confidence: 99%